Esophageal ulcer and alendronate - Ferrari Junior, Angelo Paulo; Domingues, Sérgio Hernani Stuhr (São Paulo Medical Journal, 1998)
OBJECTIVE: To describe a case of esophageal ulcer associated with the use of alendronate. CASE REPORT: This is the fifth case ever described in the literature according to our bibliographic review. In our patient, the association between the drug and the esophageal lesions was masked by the presence of a hiatal hernia, potentially a cause of the esophageal lesion. The persistence of the lesions despite high doses of anti-reflux therapy called attention to the possibility of the relationship. The esophageal lesion healed soon after suspension of alendronate. DISCUSSION: The authors present a review of the literature and point to the need for diagnostic investigation, to suspend such a drug from patients who experience dyspeptic symptoms while using it.